War and mobility. Galicians in the Kingdom of Poland during World War I - Szymczak, Damian (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The period of World War I was not only a military confrontation of soldiers of fighting countries. It also significantly affected the daily lives of millions of ordinary people. One of the manifestations of this influence was war mobility. It also concerned the inhabitants of Galicia. As a result of warfare’s, the Galicians were forced to move in different directions; as soldiers, refugees, evacuated. One of the directions of Galician migration was the Kingdom of Poland, that was conquered in 1915 by the Central Powers. The influx of people from Galicia into this area can be divided into several waves. As the first came the Polish soldiers in Austrian uniforms. The next one was made up of Galician Poles served in the Austrian occupation government. Then came to the Kingdom scholars, officials, and intelligentsia invited by the authorities of the rebuilding Polish state. The Galicians were not always well received by their countrymen from the Congress Poland. One of the reasons was prevailing stereotypes and prejudices. However, the Galician’s made a significant contribution to the work of building Polish statehood.

Okres I wojny światowej to nie tylko konfrontacja militarna żołnierzy walczących państw. Wpłynął on również istotnie na życie codzienne milionów zwykłych ludzi. Jednym z przejawów owego wpływu była wojenna mobilność. Dotyczyła ona również mieszkańców Galicji. Na skutek działań wojennych Galicjanie zostali zmuszeni do przemieszczania się w różnych kierunkach jako żołnierze, uciekinierzy, ewakuowani, pracownicy. Jednym z kierunków galicyjskich migracji było opanowane w 1915 r. przez państwa centralne Królestwo Polskie. Napływ Galicjan na ten obszar można podzielić na klika fal. Pierwszą stanowili Polacy-żołnierze w austriackich mundurach. Kolejną tworzyli galicyjscy Polacy zatrudnieni w austriackim aparacie okupacyjnym. Następnie do Królestwa przybywali uczeni, urzędnicy, inteligencja zapraszani przez władze tworzącego się państwa polskiego. Galicjanie nie zawsze spotykali się z przychylnym przyjęciem rodaków. Jedną z przyczyn były panujące stereotypy i uprzedzenia. Galicjanie wnieśli jednak istotny wkład w dzieło budowy państwowości polskiej.
Keywords: Kingdom of Poland; Galicia; World War I; mobility; migration; Królestwo Polskie; Galicja; I wojna światowa; mobilność; migracje